In-situ and model wave characterization at the Alfeite beach - Capitão, R. (2020)
In the framework of a research project entitled "BERNA", a methodology was devised to characterize the wind waves at the Alfeite beach, in the inner estuary of the Tagus river, by making in-situ measurements and using a numerical wave propagation model. With this goal in mind, a number of in-situ measurements were made, for a few selected positions in front of the Alfeite beach, at three different days, using resistive wave gauges and pressure transducers. During this period, a number of wave records, with different durations, were obtained and analyzed. Although these measurements proved to be useful to give a good insight of the main characteristics of the wind waves that might occur at that particular location, they cannot give a general characterization of the wind wave climate on the Tagus estuary, especially at the Alfeite beach, since they are a small number and are limited to a few positions only. To overcome these shortcomings, the SWAN numerical model was used to account for wave generation, propagation, attenuation and non linear interactions between wave and current phenomena in the whole estuary, in particular in the Alfeite beach. In this way, the model is applied to the same conditions of wind and tide observed on measurement days. This paper summarizes the wave characterization work performed under the BERNA project. A comparison of the SWAN results to wave parameters from wave records obtained in front of Alfeite beach is made and discussed.